Methodological Strategies that Influence the Development of the English Language Learning during the Second Semester, 2020 - Olivas, Gabriel Aurelio | Moran Mendoza, Miguel Ángel | Cortedano, Yoberlin Daniel | Alvarado, MSc. Mauricio Alvarado MSc. Mauricio (UNAN FAREM Matagalpa, 2021)
This research work is about the different learning styles during the second term 2020.This paper was focused on the influence of learning styles to develop speaking skills in students of the seventh grade at El Hular School, afternoon shift, second semester 2020.Therefore, the main objective of this research is to analyze the influence of the students’ learning styles in the development of the speaking skill. Thus, students overcome difficulties such as nervousness, pronunciation, intonation and lack fluency and vocabulary at the moment to participate in oral activities. This study has a mixed approach. Hence, it was gathered both qualitative and quantitative data. In addition, the students of the seventh grade were selected as sample size in this descriptive and applied research. Primary data were gathered through a survey, and guide observation to determine the main students’ learning styles. These data were analyzed through graphics and table. As a result, the findings showed that every student has his/her own learning styles and according to their learning styles students can develop the speaking skill in an enjoyable environment and in an easier way. Furthermore, the strategy that was conducted through different oral activities allowed finding out the students to put into practice, pronunciation, intonation, new vocabulary and fluency at the moment to pronounce the different phrases. In brief, the oral activities that include the different students’ learning styles allow they get involved in communicative activities naturally with a cheerful environment into the classroom. Keywords: Learning styles, speaking skills, strategy.